Upaya Mengurangi Keterlambatan Proses Produksi PT. Aweco Indosteel Perkasa - Rikky Yanuar; Jani Rahardjo (Jurnal Titra, 2016)
Scheduling is an important thing to determine accuracy on a project delivery to customers. Delays on a project delivery of PT. Aweco Indosteel Perkasa because of inaccurate estimated calculation processing time which makes the difference from planned schedule with the plan conditions on production. To analyze the causes of delay, used the QCC (Quality Control Circle) method to get root cause is inaccuracy of estimated calculation time jobs and uncontrolled material arrival process. Initial estimated schedule plan for polishing takes 8 shift, while based on the calculation time takes 11.24 shift and on the plan conditions takes 17 shift. This indicated that there were differences between plan time, the initial estimate, and the estimate time of calculation. Machine set up makes a difference estimated calculation, whereas the machine set up time very considered in the estimated time calculation of polishing work. Efforts to categorizing tank types based on components of the tanks was also made. Beside that, calculating time estimation in polish machine done for categorizing type of tank.